Electroacupuncture for post-stroke urinary incontinence: a systematic review and meta-analysis with trial sequential analysis - Jiang, Zefei; Zhi, Na; Liu, Guang; Sun, Xiaoxiang; Chen, Xi; Ma, Dandan; Guo, Mingming; Wang, Siying; Zhang, Hong (Frontiers in Neurology, 2023)
The evidence for the effectiveness of electroacupuncture (EA) for poststroke urinary incontinence (PSUI) patients remains unclear. Therefore, the purpose of this systematic review and meta-analysis was to assess the efficacy of EA for PSUI. Methods and analysis: Eight English and Chinese databases were searched from their inceptions until 1 August 2023 to collect randomized controlled trials (RCTs) that investigated the effect of EA on PSUI. Two reviewers independently selected studies that met the eligibility criteria, extracted the necessary data, and assessed the risk of bias for included studies using Cochrane Handbook version 5.1.0. Meta-analysis was performed using Review Manager software (version 5.4.1). Publication bias detection was conducted using STATA (version 16.0). Sequential analysis was performed using TSA 0.9.5.10 Beta. The Grading of Recommendations Assessment, Development, and Evaluation System (GRADE) was used for assessing the certainty of evidence. Results: We included 15 RCTs involving a total of 1,414 patients. The narrative analysis revealed that compared with sham EA, genuine EA exhibited greater efficacy in reducing occurrences of 24-hour urinary incontinence while also enhancing Maximum Cystometric Capacity (MCC). Moreover, this effect remained significant even during the 3-month follow-up period. Fourteen studies were encompassed within the quantitative analysis. In contrast to active interventions, EA did not yield an improvement in the responder rate (RR 1.53, 95% CI 0.61 to 3.80, P = 0.36). When compared with basic treatments, the combination of EA with them led to a reduction in 24-hour urinary incontinence occurrences (MD -0.56, 95% CI -0.60 to -0.52, P < 0.00001), an improvement in MCC (MD 43.23, 95% CI 28.86 to 57.60, P < 0.00001), and a decrease in Residual Urine Volume (RUV) (MD -19.99, 95% CI -29.75 to -10.23, P < 0.0001). However, it did not lead to an increase in the responder rate (RR 1.39, 95% CI 0.88 to 2.20, P = 0.16). In comparison to basic treatments combined with active interventions, the amalgamation of EA and them led to an increase in the responder rate (RR 1.24, 95% CI 1.14 to 1.35, P < 0.00001), a reduction in 24-hour urinary incontinence occurrences continuing.........